EXPLORING SUPERVISOR EXPECTATIONS OF HIGH-POTENTIAL EMPLOYEES: AN INVESTIGATION WITHIN THE CONTEXT OF THAI ORGANIZATIONAL CULTURE IN EASTERN THAILAND - Tanoamchard, Wanvicechanee (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2023)
High potential employees are a valuable asset to any organization as they are viewed as potential future leaders. They possess high levels of skill, knowledge, and motivation and are often identified as a key talent pool for the organization. Therefore, it is crucial for organizations to understand the expectations of these employees towards their supervisors, who play an important role in developing and retaining this group of employees. To address this issue, this article presents a qualitative research study that aims to examine the expectations of high potential employees towards their supervisors. The study employs a grounded theory research strategy with a theoretical sample of high potential employees in private sector organizations. Data were collected through in-depth interviews using an interview guideline. The study collected data from 58 organizations and 63 informants, and data collection continued until data saturation was reached. This study found that high potential employees have five key expectations from their supervisors: clear expectations, opportunities for growth and development, regular feedback, support and guidance, and recognition and rewards. These expectations are crucial for enhancing the retention, job satisfaction, and overall performance of high potential employees in organizations. The findings of this research have broader implications for talent management practices, organizational development, and leadership strategies within private sector organizations. The in-depth exploration of high-potential employees' experiences offers valuable insights for organizations seeking to optimize the potential of their top performers and cultivate a culture of continuous growth and development.